Empowering Literature For Educating Character Building (A Study Case On Readers Of O. Henry's After Twenty Years) - Trisnawati, Ririn Kurnia (Journal of English and Education (JEE), 2012)
When Martin Luther King, Jr. mentioned that “We must remember that intelligence is not enough. Intelligence plus character that is the goal of true education”, he must have completely understood that education is never enough without educating the students' characters. Nowadays, characterbuilding-based curriculum has been promoted throughout the country to educate students' character building. It also soon becomes the government's concern and urgency to teach character building to students of any level as it is mentioned in the Decree of National Education Ministry number 045/U/2002. However, there are some problematic matters in designing its teaching materials whether it is between didactic and non-didactic or implied and vice versa method of teaching. To propose a prospective solution of teaching character building to students; therefore, this paper aims to probe and to share a case study from the readers of O. Henry's After Twenty Years who happen to be the students of Book Report class at English Language and Literature Department of Jenderal Soedirman University in Purwokerto Central Java. The short story is given to the students as the teaching material to seek the most efficient way of teaching them character building as it is reflected within the short story. Given the short story, read it, responded and finally answered the questionnaire, those students are able to identify the character building embedded in that particular literary work and to learn them from the story. Besides, derived from the students' questionnaire, it can be concluded that students can educate themselves the character building through the story by mentioning those learned characters, and they also can show their selfreflection after learning it. In conclusion, there is possibility of using literature as prospective teaching material in educating students' character building by analyzing the qualities embedded in the literature e.g. novels, short stories and poems, and doing this is also a way of empowering literature for a greater life benefit.Keyword: Character building, Teaching material, and Literature empowerment